DIFFRENTIALS IN EXTERNAL, INTERNAL AND PRACTICAL MARKS OF STUDENTS IN B.ED EXAMINATION - Kaur, Sarbjit (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
The word examinations bring shivers to all right from children to adults, leading to trembling hands, parched lips, pounding heart and sleepless nights. It has formed an inseparable adjunct of our everyday life through ages. It has been accepted by all concerned that examination (in some form) is necessar Examinations are as old as the human society. Examinations can be classified in a number of ways, taking into account the nature of the examining authority, the method used in examining the pupils and the frequency of examinations. Regarding the nature of examining authority, the examinations may be either external or internal. Internal examinations are conducted by educational institutions from time to time, for evaluating the progress of students for grading them. The external examinations come generally at the end of each session. The university examinations and the board examinations are the examples of external examinations